Li homini se pretendono essere patroni. Alpine Lombardy Hospitals in the jurisdictional and social tensions of the late Middle Ages (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
To summarise the situation of the late medieval hospitals in the alpine area of Lombardy, it may seem obvious to use the label of crisis to emphasise the extinction of the communities of fratres and sorores who originally had dedicated their lives to the needy, the fading of the religious identity of the ministers who governed them, the appropriation of the hospitals‘ patrimonies into benefices for the clergy, the need for rural dwellers to have recourse to the reformed urban hospital of Como, the preference for ritual alms rather than donations to hospitals by large and small benefactors. However, when the picture is more subtly articulated there are a few examples of continued vitality. While it is true that hospices in mountain passes had often lost their function and various rural institutions were assimilated into simple chapels providing only sacramental services, in some borghi (small towns) the hospitals continued to perform a wide range of social functions. The vitality or decline of a hospital was profoundly influenced by its geographical location, and the dynamics of jurisdictional conflicts between the ecclesiastical hierarchy, local powers (lords and communities) and central authorities. More effective than their competitors were the borghi communes, particularly in the Ticino area, and the valley community in Valcamonica, led by their elites, even if these elites were not allowed to take a dominant role. The local institutions ensured the functioning of the hospitals, which may have been small but were very active in housing foreigners, the poor and the sick or supporting abandoned children.
Keywords: Later Middle Ages; Lombardy; Alps; charity; hospitals; communities; towns; local lords; ecclesiastical institutions